2014
DOI: 10.1007/s00540-014-1793-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local infiltration analgesia for posterior knee pain after total knee arthroplasty: comparison with sciatic nerve block

Abstract: The combination of FNB and PIA provides sufficient analgesia after TKA. The rapid and convenient periarticular infiltration technique could be a good alternative to SNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…Five trials that compared SNB with various analgesic modalities, but lacked an appropriate FNB control group, were also excluded. 15,18,20,22,23 A single relevant RCT comparing single-shot FNB to single-shot FNB ? SNB was identified in the trial registries (clinical trials registry NCT02135120, relevant sample size = 30), but it was still in the recruitment phase with no available outcome results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five trials that compared SNB with various analgesic modalities, but lacked an appropriate FNB control group, were also excluded. 15,18,20,22,23 A single relevant RCT comparing single-shot FNB to single-shot FNB ? SNB was identified in the trial registries (clinical trials registry NCT02135120, relevant sample size = 30), but it was still in the recruitment phase with no available outcome results.…”
Section: Resultsmentioning
confidence: 99%
“…Such small RCTs could increase the likelihood of detecting a treatment effect and/or misestimating its magnitude because of a combination of mere chance and publication bias. Third, analgesic techniques other than SNB (e.g., intra-articular local anesthetic infiltration, 18,23 posterior knee capsule injection 56 have achieved effective pain relief following TKA, whether in combination with or as substitutes for SNB. The influence of the aforementioned analgesic options on SNB analgesia is not within the scope of our systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed alternatives to sciatic nerve block include LA infiltration of the posterior capsule of the knee joint, selective tibial nerve block,384 and sensory posterior articular nerve of the knee (ie, SPANK) block 385. Posterior capsular infiltration remains controversial, as Gi et al 386 found it to a be viable alternative to sciatic nerve block whereas Safa et al 387 and Pinsornak et al 388 concluded that it confers no additional analgesia when combined with femoral nerve block or standard LA infiltration of the knee, respectively. Although selective tibial nerve block spares the peroneal nerve (and prevents the occurrence of foot drop), its impact on ambulation and rehabilitation remains unknown.…”
Section: Controversial Areas Related To Outcomesmentioning
confidence: 99%
“…48,49 Pain from the posterior knee region after TKA is probably not from the posterior part of the knee capsule, because it is not intersected during surgery. It is rather referred pain from the intra-articular innervation.…”
Section: Strategy To Block Knee Pain From the Posterior Nerve Groupmentioning
confidence: 99%